3 - The Growth of Islamic Learning in Northern Ghana and Its Interaction with Western Secular Education: DOI: 10.4314/ad.v30i1.22212 - Iddrisu, Abdulai (Africa Development, 2005)
This paper examines the growth of Islamic learning in northern Ghana and its in teraction with western secular education. It argues that colonial policies and prac tice had far-reaching implications for Islamic learning, stifling attempts at growth, and suggests that the contemporary situation with regard to Islamic learning in Ghana cannot be properly understood without an appreciation of the historical forces that have helped fashion this system of learning. It concludes that there is need for a meaningful and sustainable interaction between Islamic and Western secular edu cation, especially in the era of decentralisation and increased demand for new com petence at local levels